Online risks and parental mediation in social media usage among kids: a quantitative study in Rawalpindi City - Youssef, Enaam; Ali, Sana; Al Malek, Mahra; Riaz, Saqib (Frontiers in Communication, 2025)
This research investigates different aspects of online media usage among children and the dynamics surrounding it. It aims to determine the patterns of online media consumption among children and comprehend their perceptions concerning exposure to inappropriate content online. This research is supported by the Parental Mediation Theory and quantitative design to examine children’s online experiences. Data gathered from 346 respondents revealed that the respondents indicated high-level engagement in online media, mainly for surfing and instant messaging, with daily usage varying from 1 to 3 h and some exceeding five hours. Respondents have personal accounts on more than four social networking sites, with Facebook being the principal platform. Concerning vulnerability to online indecent content, respondents emphasized examples of accidental exposure during online activities, i.e., surfing and instant messaging, mostly occurring at home and school. The frequency of exposure was usually categorized as occurring four or more times, leading to possible risks and hazards to children’s well-being. The study further highlighted children’s perceptions of parental mediation in online media use. Therefore, this study emphasizes the importance of programs empowering parents with the knowledge and abilities to handle and manage their children’s online media activities adeptly. Also, maintaining a balance between using the educational benefits of online media and protecting children from possible risks becomes crucial, highlighting parents’ significant role in this critical domain. Finally, this research proposed some implications, and limitations are discussed accordingly.